2015
DOI: 10.2196/mededu.4580
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Pilot Educational Psychiatry Website: Opportunities, Barriers, and Next Steps

Abstract: BackgroundWhile medical students and residents may be utilizing websites as online learning resources, medical trainees and educators now have the opportunity to create such educational websites and digital tools on their own. However, the process and theory of building educational websites for medical education have not yet been fully explored.ObjectiveTo understand the opportunities, barriers, and process of creating a novel medical educational website.MethodsWe created a pilot psychiatric educational websit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…With the increased use of digital learning tools in medical education, web tools remain the most frequently utilized digital resource among medical students and residents [ 12 ]. A recent survey study of an inpatient medicine team found that web-based learning interventions improved self-directed learning, communication goals, and learning environment among medical students and residents [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the increased use of digital learning tools in medical education, web tools remain the most frequently utilized digital resource among medical students and residents [ 12 ]. A recent survey study of an inpatient medicine team found that web-based learning interventions improved self-directed learning, communication goals, and learning environment among medical students and residents [ 13 ].…”
Section: Introductionmentioning
confidence: 99%